Efektivitas PERMA Nomor 1 Tahun 2016 Tentang Mediasi dalam Perkara Perceraian di Pengadilan Agama Purwakarta - Dadang Jaya; Dudun Najmudin (LEX FAMILIA: Journal of Islamic Family Law, 2026)
Divorce has been explicitly regulated in the Marriage Law Article 39 paragraph (1) which states that divorce can only be carried out before a court hearing after the court concerned has tried and failed to reconcile the two parties. Likewise, the affirmation in the Compilation of Islamic Law (KHI) states that divorce can only be carried out before a Religious Court hearing. This is implemented in order to make it difficult for divorce to occur in society and as a form of orderly population administration. The form of effort made by the court to reconcile the two parties who insist on going through a divorce is by requiring them to undergo a mediation process in the first instance court environment, both the District Court and the Religious Court. The implementation of Mediation in the first instance court environment in Indonesia for all civil cases became mandatory after the enactment of the Supreme Court Regulation (PERMA) hereinafter abbreviated as PERMA Number 2 of 2003 concerning Mediation Procedures in Court which has now been updated to PERMA Number 1 of 2016 concerning Mediation Procedures. With the obligation to undergo a mediation process for all civil disputes submitted to the court, it aims to find common ground and reach a consensus between the two disputing parties assisted by a mediator to reach an agreement so that in this case divorce can be minimized, as well as with a faster, simpler and cheaper settlement process. The efforts that have been made by the Supreme Court towards the settlement of civil disputes in court through PERMA Number 1 of 2016 certainly need to be optimized, not just a mere formality and not seriously trying various appropriate steps to reconcile the dispute. The effectiveness of mediation in court is very important to continue to be maximized, because it often happens that the parties being mediated no longer care about the agreement and/or the mediator is considered unfit to mediate the case; either because they are only carrying out their duties or the mediator has not obtained a mediation certificate as proof that the mediator has special expertise and tends to carry out the mediation process which is not much different from his previous role as a judge. This can be seen from the level of success of mediation in court, where the mediation success rate when compared to all cases received by the court is only below 10% which are declared successful mediation. Based on the explanation above, the mediator has a very important role in this case to reconcile divorce cases that go to court to reconcile and find an agreement for both parties. However, there is a fact that in the Purwakarta Religious Court the judge who also serves as a mediator does not have a mediator certificate and the busyness of the trial affects the quality of mediation achievements. Therefore, the author will examine in the form of research on how effective mediation is in court after the enactment of Supreme Court Regulation Number 1 of 2016 concerning Mediation in Court.